The effect of tribological processes on productivity: a case study of industries in Ibadan metropolis of Nigeria (2009)
This study analyzed the connection between tribological and other forms of processes in manufacturing industries to productivity in such outfits. Results from the study showed that 54% of the visited industries recorded the highest hours of downtime due to tribological processes, while,15% and 31% of the industries had the highest downtimes hours resulting from electrical and other processes respectively. Also 23% of the total industries were observed to have more electrical faults, 31% recorded highest tribological issues, while 46% had more of non-tribological non-electrical faults.